The Effectiveness of Islamic Gratitude Psychoeducation Groups in Improving Student Resilience - Anila Umriana (Bulletin of Counseling and Psychotherapy, 2026)
This study aims to examine the effectiveness of Islamic Gratitude psychoeducation groups in improving student resilience. The study used a pretest–multiple posttest control group quasi-experimental design. The experimental group received the Islamic Gratitude psychoeducation group intervention, while the control group received a placebo intervention. Each group consisted of 8 students. The resilience instrument used was the Taormina Resilience Scale (APRS). Resilience was measured through pretest, posttest, and follow-up stages. The data were analyzed using Repeated Measures ANOVA after fulfilling the assumptions of normality and homogeneity of variance. The results of the analysis showed a significant increase in resilience in the experimental group compared to the control group, as well as a significant interaction between the measurement time and the group, indicating the effectiveness of the Islamic Gratitude intervention in continuously improving student resilience. These findings indicate that the Islamic Gratitude psychoeducation group is an effective and relevant intervention to be applied in Islamic value-based guidance and counseling services in higher education.